Water-stable perovskite-on-polymer fluorescent microspheres for simultaneous monitoring of pH, urea, and urease - Sanjiv Sharma (Analytical and Bioanalytical Chemistry, 2021)
Perovskite materials have attracted attention due to their excellent optical and electrical properties; however, their unsatisfactory stability limits their application in biochemical detection. In this paper, CsPbBr3 perovskite quantum dots were successfully encapsulated in poly(styrene/acrylamide) microspheres, using a swelling–shrinking method. The manufactured perovskite microspheres (PDPS composites) not only maintained strong photoluminescence (PL) stability but also demonstrated great water solubility. Additionally, a real-time pH monitoring platform was constructed based on the prepared PDPS composites and dopamine, and the system showed a good linear relationship in a pH range of 4–12. Furthermore, urea could be hydrolyzed to produce hydroxyl groups, thereby increasing the pH of the solution. Therefore, this system was then extended for urea and urease detection. As a result, the detection limits of urea and urease were recorded as 1.67 μM and 2.1 mU/mL, respectively. This development provides an interesting demonstration of the expanding list of applications of perovskite materials.